Comprehensive Review of the ThinkFirst Injury Prevention Programs: A 30‐Year Success Story for Organized Neurosurgery. Issue 3 (September 2017) - Youngers, Emily H.; Zundel, Kayt; Gerhardstein, Deborah; Martínez, Mariela; Bertrán, Carlos; Proctor, Mark R.; Spatola, Mark A.; Neuwelt, Edward A.
Abstract : N/A: Traumatic brain and spinal cord injuries are major public health issues causing significant death and long‐term disability in the United States, with higher incidences in young and older adults. The ThinkFirst National Injury Prevention Foundation is a nonprofit organization focused on injury prevention education and awareness for people of all ages, with a particular focus on educating children, teens, and young adults. ThinkFirst chapters have evaluated the effectiveness of the ThinkFirst programs in both children and teens by demonstrating significant improvement in knowledge regarding high‐risk behaviors postintervention. Here, we review the available literature studying the efficacy of the ThinkFirst National Injury Prevention Foundation programs, outline current ThinkFirst activity, and discuss future directions of the program. This review discusses the efforts of a number of ThinkFirst chapters in terms of research, legislation, and public communication. It showcases the success of ThinkFirst interventions and suggests future directions which can help improve national injury prevention efforts.